2020
DOI: 10.3390/f11111210
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and Structural Aspects of In Vitro Somatic Embryogenesis in Abies alba Mill

Abstract: Initiation of somatic embryogenesis from immature zygotic embryos, long-term maintenance of embryogenic tissue in vitro or by cryopreservation, as well as maturation, of somatic embryos of Abies alba Mill. are reported in this study. For the initiation of embryogenic tissues, a DCR medium containing different types of cytokinins (1 mg.L−1) were tested. During three consecutive years, 61 cell lines were initiated out of 1308 explants, with initiation frequencies ranging between 0.83 and 13.33%. The type of cyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 54 publications
2
16
0
Order By: Relevance
“…Our current investigations revealed that BAP applied alone on SH medium gave the best EC proliferation rate compared to 2,4-D which gave no results if applied alone and caused a remarkable decrease of the EC proliferation rate if combined with BAP. These results are in line with those obtained for Abies fraseri, A. normanniana, A. alba, and Greek fir, where cytokinin was the exclusive PGR used to induce and maintain the ET (Salaj et al 2020;Kim et al 2009;Krajňáková et al 2008, Vookovà et al 1998Nørgaard and Kgrostrup 1995). The present work, reports the first successful somatic embryogenesis obtained from mature zygotic embryos of Abies nebrodensis (Fig.…”
Section: Encapsulation and Cryopreservation Assaysupporting
confidence: 86%
See 2 more Smart Citations
“…Our current investigations revealed that BAP applied alone on SH medium gave the best EC proliferation rate compared to 2,4-D which gave no results if applied alone and caused a remarkable decrease of the EC proliferation rate if combined with BAP. These results are in line with those obtained for Abies fraseri, A. normanniana, A. alba, and Greek fir, where cytokinin was the exclusive PGR used to induce and maintain the ET (Salaj et al 2020;Kim et al 2009;Krajňáková et al 2008, Vookovà et al 1998Nørgaard and Kgrostrup 1995). The present work, reports the first successful somatic embryogenesis obtained from mature zygotic embryos of Abies nebrodensis (Fig.…”
Section: Encapsulation and Cryopreservation Assaysupporting
confidence: 86%
“…A significant effect of donor trees on the callus induction rates was reported, where tree IN8 showed the best induction rate (40%) compared to the other tested donor trees. The callus induction rate obtained in A. nebrodenesis is greater than those reported by Von Arnold (1987) for Picea abies (8%), by Szczygieł and Kowalczyk (2001) for Abies alba (1.2 to 29.4% of callus initiation on mature embryos), by Salaj et al (2020) who recorded 0.83-13.33% of initiation frequencies from Abies alba mill, and by Gao et al (2019) who reported a callus induction rate of 1.67% for Pinus korainesis. This heterogeneity in callus induction rates could be explained and highly related to the donor trees age and maturity (Humánez et al 2013;Niskanen et al 2004).…”
Section: Encapsulation and Cryopreservation Assaymentioning
confidence: 51%
See 1 more Smart Citation
“…According to Korpel (Jaworski) [3], forests with dominant fir have a development cycle of 400 years. The tree has been subject to numerous studies, including [15][16][17][18][19]. Just one periodical, called 'Sylwan', has printed over 40 publications during the last ten years.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have reported different aspects of the application of somatic embryogenesis in woody plants, either to induce somatic embryos or to produce genotypes that display tolerance to biotic or abiotic stress. For example, Salaj et al [4] described SE induction in immature zygotic embryos, the long-term maintenance of embryogenic tissue in vitro or by cryopreservation and also the maturation of somatic embryos in an economically important conifer species, Abies alba Mill. These researchers obtained induction frequencies ranging from 0.83% to 13.33%, although the different cytokinins evaluated did not have significantly different effects.…”
mentioning
confidence: 99%